A new iridescent “elfin” butterfly species of Podanotum (Lepidoptera: Lycaenidae: Eumaeini) from the Colombian Andes - Prieto, Carlos; Rodriguez, Gabriel (Zootaxa, 2012)
A new butterfly species, Podanotum pulsar Prieto & Rodríguez n. sp. is described from the high Andes of Colombia. Wepresent a brief discussion on its systematic placement and on adult ecology. Adult specimens and the genitalia of the male andfemale are illustrated and compared with the most closely related species Podanotum glorissimum Bálint & Wojtusiak, according to morphological characters.